Marijuana Use and Depressive Symptoms; Gender Differences in African American Adolescents - Assari, Shervin; Mistry, Ritesh; Caldwell, Cleopatra Howard; Zimmerman, Marc A. (Frontiers in Psychology, 2018)
Background. This study aimed to examine gender differences in the bidirectional associations between marijuana use and depressive symptoms in Black youth. The study also tested gender differences in the associations between socioeconomic status, maternal support, and friends’ drug use with depressive symptoms and marijuana use. Method. This is a secondary analysis of the Flint Adolescent Study (FAS). 681 Black youth (335 males and 346 females) were followed for 3 years, from 1995 (mean age 16) to 1997 (mean age 19). Depressive symptoms (Brief Symptom Inventory) and marijuana use were measured annually from baseline to the end of follow up. We used multi-group latent growth curve modeling to explore the reciprocal associations between depressive symptoms and marijuana use over time based on gender. Results. Baseline marijuana use was predictive of an increase in depressive symptoms among male but not female Black adolescents. Baseline depressive symptoms were not predictive of an increase in marijuana use among male or female adolescents. Although having an intact family and friends’ drug use were similarly associated with baseline and change in marijuana use males and females, there were gender differences in the association between maternal support and depressive symptoms. Conclusion. Study data suggest that male Black youth who screen positive for marijuana use should also be evaluated for depressive symptoms and vice versa. Interventions that combine treatment for marijuana use as well as depressive symptoms may be indicated for black male youth.